2 '- (5-chloro-1H-indol-3-yl)methylene 2-(1H-indol-3-yl)acetohydrazide - Ali, Hapipah Mohd; Ng, S.W.; Jefrey, B.W.; Shimar, J.N. (International Union of Crystallography, 2007)
The molecules of the title compound, C19H15ClN4O, are linked into a three-dimensional architecture by N - (HO)-O-... interactions.